USING OF ALUMINIUM ALLOYS WITH INCREASED CONTENT OF IRON - V. A. Kalinchenko; B. M. Nemenenok; G. V. Dovnar (Литьë и металлургия, 2007)
The influence of iron on mechanical, technological^, and service characteristics of some aluminium alloys is estimated. It is determined that iron decreases fluidity, degrades mould-fillability and increases inclination of aluminium alloys to hot cracks forming. The influence of cooling speed on sizes of impurities FeAl3 in alloys of system Al-Fe and concentration of iron in hard solution is studied.